2002
DOI: 10.1002/hup.467
|View full text |Cite
|
Sign up to set email alerts
|

Use of paroxetine for the treatment of depression and anxiety disorders in the elderly: a review

Abstract: Paroxetine is a potent selective serotonin reuptake inhibitor (SSRI) with indications for the treatment of depression, obsessive- compulsive disorder, panic disorder and social phobia. It is also used in the treatment of generalized anxiety disorder, post-traumatic stress disorder, premenstrual dysphoric disorder and chronic headache. There is wide interindividual variation in the pharmacokinetics of paroxetine in adults as well as in the elderly with higher plasma concentrations and slower elimination noted i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…Numerous adverse effects from the use of antidepressant therapy have been reported 70,77–82 (Table 3). Serotonin toxicity (symptoms such as, e.g.…”
Section: Treatments For Depression and Anxiety In Copd Patientsmentioning
confidence: 99%
“…Numerous adverse effects from the use of antidepressant therapy have been reported 70,77–82 (Table 3). Serotonin toxicity (symptoms such as, e.g.…”
Section: Treatments For Depression and Anxiety In Copd Patientsmentioning
confidence: 99%
“…For example, serotonin may enhance synaptic plasticity by activating cyclic AMP response element-binding protein (CREB) and up-regulating the expression of brain-derived neurotrophic factor (BDNF) (reviewed by Pang and Lu, 2004), and this signaling mechanism may be compromised in AD (Tong et al, 2001). Serotonin-selective reuptake inhibitors are widely prescribed for the treatment of clinical depression and anxiety disorders (Wagstaff et al, 2002;Bourin, 2003), but may also have therapeutic potential as neuroprotective agents (Sanchez et al, 2001;Duan et al, 2004). It was recently reported that environmental enrichment (Lazarov et al, 2004) and dietary restriction (Patel et al, 2005;Wang et al, 2005) can reduce Aβ deposition in APP mutant mice.…”
Section: Introductionmentioning
confidence: 99%
“…In seriously incapacitating cases, when comorbid severe depression is present, and in older adults reluctant to start a psychological treatment, SSRIs can be a suitable alternative. The available data imply that SSRIs are as effective in older adults as in mixed-age populations in reducing anxiety, and that they are generally well-tolerated [20,44]. One recent meta-analysis even suggests that SSRIs may be more effective in reducing late-life anxiety than psychological interventions [26], but as the available research data are scarce and hampered by various methodologic shortcomings, this conclusion is premature.…”
Section: Pharmacologic Interventionsmentioning
confidence: 85%